Assessement of ICT Literacy Level among Senior Schools Biology Teachers in Kwara State, Nigeria - LUWOYE, AKINDEYI; Afolabi, Ojo Kayode; Adesanya, Emmanuel A (Universitas Islam Negeri Walisongo Semarang, 2025)
Information and communication technology (ICT) has become an important tool in all aspects of life ranging from medicine to security and education. It is an indispensable part of education system and has brought about quality education. This study, therefore, assessed ICT literacy level of senior school biology teachers' in Kwara State, Nigeria. The study investigated the influence of age, teaching experience and gender on ICT literacy level among senior school biology teachers in Kwara State. The study was a survey research type. The sample comprised of two hundred and fifty-nine (259) biology teachers from one hundred and nineteen (119) public & private senior secondary schools in Kwara State. Purposive sampling technique was adopted. The instrument entitled